Dobrodružství historické interpretace - Klápště, Jan (Masaryk University Contributions to History, 2021)
Title in English: The Adventure of Historical Interpretation This collection of nineteen essays written by prominent historians demonstrates the diversity of academic approaches. Their work with historical sources, the foundation stone of research, is combined with ethical and aesthetic decision-making, which forms an indisputable part of their work. This is often surprising - both for the readers and themselves. It represents a great intellectual adventure. They cannot invent sources or set arbitrary rules, plots, and twists and turns, as a novelist might. However, they can write a scientific work which is the result of a creative approach.